Achieving Equality of Opportunity Through a Universal Endowment System for French Youth - Planel, Niels (Sens public, 2018)
This essay makes the case for a universal endowment system for the youth in France. Building on principles inspired by the works of Thomas Paine and John Rawls, it proposes that any French citizen reaching the age of 18 is endowed with the amount of € 50,000 disbursed over a six-year period to fund projects such as starting a business, acquiring real estate or financing college.